Stunting and its associated factors in under-five children: evidence from Bangladesh Demographic and Health Survey 2014 - Md Sahidul Islam; Md Saimul Islam; Rajib Chowdhury; Mohammad Mostafa Zaman (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Impaired growth and development experienced by children, referred to as stunting, is a major impediment to human development. Although the Bangladesh economy has experienced high growth in recent decades, malnutrition still remains a public health problem. This study assesses the prevalence and risk factors associated with stunting among children under-five in Bangladesh. This analysis uses data from the Bangladesh Demographic and Health Survey 2014, a community-based cross-sectional study. A total of 6,965 children were enrolled in the study. The prevalence of stunting was 36.5% [95% confidence interval (CI): 34.8-38.3%] and 40.2% [95% CI: 37.4-43.1%] for children aged 0-59 months and 0-23 months respectively. Multivariate logistic regression revealed that the significant factors for stunting for children aged 0-59 months and 0-23 months were maternal working status, mother education, mothers age at childbirth, birth order, delivery mode, receiving antenatal clinic visit, media habits, perceived size of child at birth, child sex, children having had diarrhea in last two weeks, wealth and geographical region. In order to meet the nutrition indicators under zero hunger sustainable development goal and 2025 target of World Health Assembly, policy interventions are needed to reduce stunting specially focusing on eastern region of Bangladesh.